Lightweight photovoltaic modules technologies: reliability evaluation and market opportunity - Dupuis Julien; Abdel Nour Christine; Oliveira Santos João Victor; Lefillastre Paul (EPJ Photovoltaics)
This study aims at performing an assessment of lightweight photovoltaic (PV) module's reliability by comparing module's performances and reliability of several manufacturers. Lightweight modules are characterized by a reduced weight compared to classical PV modules with usually less than 10 kg/m2 allowing its installation on rooftops with low bearing capacity without the need of reinforcing the roof structure. Even if this PV technology has higher costs than classical modules due to lower capacity production and often specific module material like transparent composite instead of glass, it represents an efficient technical and commercial solution for specific applications with lower transportation, installation, and maintenance costs. Nevertheless, very few information is available on the reliability of these emerging products. The large variety of module components used by the manufacturers do not help into selecting the best modules available on the market. In this work, after introducing the potential capacity of low bearing rooftop market for France, we detailed a first reliability benchmark of market available lightweight module's products. This benchmark was carried out through indoor experimental work under accelerated aging testing as well as outdoor exposure conditions based on IEC61215 and IEC61730 qualification standards. The accelerated aging sequence results highlight high power degradation discrepancies between the five technologies investigated with some of them degrading more than 50% after a damp heat − UV − thermal cycling testing sequence. The power generation obtained in outdoor conditions underlines lower energy yield obtained by installing photovoltaic module directly on a flat roof caused by their orientation and tilt (0 to 10°) entailing sometimes higher soling losses. Based on all these results, LCOE estimations are performed and show an over-cost between 10 and 100% compared to the use of standard module option with roof reinforcement.